TEKNIK PRODUKSI PAKAN BUATAN DI BALAI PERIKANAN BUDIDAYA AIR PAYAU (BPBAP) SITUBONDO JAWA TIMUR - Veni Darmawiyanti; Baidhowi Baidhowi (Faculty of Science and Technology University Ibrahimy, 2015)
This research was conducted at the Laboratory of Brackish Water Aquaculture Nutrition Center Situbondo, East Java in February until April 2015 in order to know how to manufacture artificial feed and artificial feed quality test results. The method used in this research is survey. Primary data is taken through observation, interviews, documentation and participation. Secondary data was collected through literature associated with the study material. Production of artificial feed in Situbondo BPBAP consists of a series of the following stages: selecting raw material feed formulations determination, flouring, sifting, weighing, mixing raw materials, printing, drying, packaging and storage of feed. Chemical Test Results artificial feed quality is as follows: the feed water content (8.09%); ash content (10.05%) levels of protein content 38%, fat content 7.62% and 2.38% crude fiber. As for the physics test hasili obtained 98.4%